PERANAN KONSELOR ADIKSI DALAM PEMULIHAN PECANDU NARKOBA DI REHABILITASI NARKOBA SIBOLANGIT CENTRE - Harahap, Nurintan Muliani; Siregar, Siti Wahyuni; Alawiyah, Desi (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
Drug and illicit drug abuse in Indonesia in recent years has become a serious problem and has reached a concerning state to become a national problem. In the implementation of recovery, drug addicts need to undergo a recovery process with an effective program and carried out in a rehabilitation center and assistance from professional staff. The professional staff needed by addicts to recover are addiction counselors, psychologists, doctors, religious leaders and a supportive environment. This study aims to determine what programs are run by addiction counselors at the Sibolangit Rehabilitation Center in the process of recovering drug addicts, to determine the role of addiction counselors in the recovery of drug addicts and to determine the supporting and inhibiting factors in the recovery of drug addicts at the Sibolangit Rehabilitation Center. This study is a field study with a qualitative descriptive nature using observation, interview and documentation techniques in order to obtain data and information in this study. The results of this study indicate that the program run by drug addicts or residents at the Sibolangit Rehabilitation Center is adjusted to the Therapeutic Community (TC) method which requires active participation, feedback, role modeling, collective change formats, sharing, structural and systematic, open communication, group relationships and using unique terminology. Addiction counselors play a full role as facilitators and companions during the recovery period. Starting from conducting an assessment at the beginning of recovery, meeting needs during the recovery program and continuing to provide aftercare services after completing the recovery program in order to maintain recovery through the family and the openness of the residents themselves. Supporting factors for the recovery of drug addicts are strong self-motivation, family conditions that support recovery, positive friendships and a drug-free living environment. While the inhibiting factors for the recovery of drug addicts are a lack of self-confidence, a busy and less attentive family, friends who still consume drugs, and a living environment that contains a drug environment.